(untitled) (Vietnam Journal of Community Medicine, 2022)
From January 2021 to June 2021, we conduct monitoring and evaluation of the working environment and the management of occupational safety and health at the AC roof sheet production facility of “ Dong Anh Building Materials Roofing Joint Stock Company” we obtained the following results: The percentage of samples measured for microclimate factors did not meet the allowable standards was 10.7%. The percentage of total dust samples exceeding the permissible standard is 2.1%, no samples of asbestos fiber dust and respiratory dust exceeding the permissible standards. The content of occupational safety and health management has been well implemented, accounting for 71.5 - 100%. On site inspection, the percentage of units that strictly comply with regulations on occupational safety and health is not high, accounting for 25 - 43.8% depending on each specific indicator.